Effectiveness of a web platform on university students' motivation to quit smoking - Alba María Romero-López; Silvia Portero-; Manuel Vaquero-Abellán (Universidade de São Paulo, 2020)
Objective: to know the dependence on nicotine and the motivation to quit smoking in Nursing and Physiotherapy students of a university in the South of Spain, and to evaluate the impact of an intervention based on the use of information technologies on the motivation to quit smoking. Method: a pilot study in two phases: the first being cross-sectional and the second, a before-and-after intervention. The motivation to quit smoking was assessed by means of the Richmond questionnaire, and the dependence on nicotine through the Fagerström questionnaire; additionally, an intervention was performed based on the use of a web platform to increase motivation to quit smoking. Descriptive and inferential statistics were applied. Results: the prevalence in the use of tobacco was 4.33% (n=29). 3.45% of the participants had a high level of dependence; and 6.90%, a high level of motivation. The level of motivation did not change after the intervention (p=0.10). Conclusion: most of the students have low levels of motivation to quit smoking and of physical dependence to nicotine. The level of motivation to quit smoking does not change after performing the intervention.